Peningkatan Pemahaman Dan Penalaran Logis Siswa Smp Menggunakan Teknik Probing Pada Kelompok Kecil - Baihaki, Oih (Pasundan Journal of Mathematics Education : Jurnal Pendidikan Matematika, 2014)
This study aims at examining the increasing understanding of mathematical ability and logical reasoning of students receiving learning with probing techniques with students receiving regular teaching and examining students' attitudes toward learning with the use of probing techniques. This study is a quasi-experimental design with nonequivalent control group. This study population is one of the main Junior High School students in Sumedang, while class VIII student research samples as many as two grades. One class became the experimental group and the class into groups and one control. The instruments used in this study were to test the understanding of mathematical and logical reasoning of students in the description form, and the scale of attitude towards learning by using probing techniques. The results showed that: 1) The ability of students to gain an understanding of mathematical learning with probing technique is better than the learning of students who receive regular teaching 2) Logical reasoning ability of students receiving learning with probing techniques are better than students who receive regular learning, 3) Improved understanding of the mathematical ability of students receiving learning with probing techniques are better than students who receive regular learning, 4) Increased Logical reasoning ability of students receiving learning with probing techniques are better than students who receive regular learning, 5) The attitude of students towards learning by using probing techniques demonstrate a positive attitude.